An Efficient Green Protocol for Synthesis Of 2,3-Dihydroquinazolin-4(1H)-Ones Using Mandelic Acid Under Solvent-Free Conditions - S. G. Sonkamble,; J. R. Deshmukh,; U. N. Chaudhar,; A. M. Patil, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Green and convenient synthesis of 2,3-dihydroquinazolin- 4(1H)- one derivatives (DHQ) from condensation of 2-aminobenzamide and various aromatic aldehydes using Mandelic acid under Solvent‐Free Conditions. The present method has some important advantages such as mild reaction conditions, use of naturally occurring commercially available low cost organocatalyst, short reaction times and high yields with the green protocol by avoiding toxic catalysts and solvents, column chromatography-free purification procedure are some of the major advantages of this developed protocol.
Keywords: 2,3-dihydroquinazolin- 4(1H)- one; 2-Aminobenzamide; Aromatic Aldehydes; Mandelic acid